2022
DOI: 10.3390/s22166153
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interpolation of Gravimetric Soil Moisture Using EM38-mk Induction and Ensemble Machine Learning (Case Study from Dry Steppe Zone in Volgograd Region)

Abstract: The implementation of the sustainable management of the interaction between agriculture and the environment requires an increasingly deep understanding and numerical description of the soil genesis and properties of soils. One of the areas of application of relevant knowledge is digital irrigated agriculture. During the development of such technologies, the traditional methods of soil research can be quite expensive and time consuming. Proximal soil sensing in combination with predictive soil mapping can signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…We found that soils within the study area had no sign of salinity, with ECa values < 100 mSm −1 . The findings of this study relate to the findings of other studies [43,65], which also used the EM38-mk to estimate soil moisture based on ECa measurements, and found similar trends in terms of correlations and behavior of ECa under given SWC conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that soils within the study area had no sign of salinity, with ECa values < 100 mSm −1 . The findings of this study relate to the findings of other studies [43,65], which also used the EM38-mk to estimate soil moisture based on ECa measurements, and found similar trends in terms of correlations and behavior of ECa under given SWC conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study demonstrate that the soil water content is the main driver that allows the flow of electrical current in the soil medium, making it easier for the electromagnetic induction device to determine the soil's apparent electrical conductivity. Such findings are also reported by others [36,43,65]. The linear relationship between soil water content and the soil's electrical conductivity made it possible to easily convert ECa (mS/m) into SWC%, influenced largely by irrigation in the area.…”
Section: Discussionsupporting
confidence: 83%
“…For example, both random forest and support-vector machine provide some usersadjusted model parameters, but multiple linear regression does not provide (Han et al, 2022b;Tian and Fu, 2022). The predicted accuracies of SM estimation based on the constructed random forest models in this study were no lower than those found in earlier studies performed on (Zeng et al, 2015;Bai et al, 2017;Deng et al, 2018;Tong et al, 2021;Wu and Wen, 2022) and beyond (Zormand et al, 2017;Ma et al, 2020;Yuan et al, 2020;Zhang et al, 2022a;Wang et al, 2022c;Jarray et al, 2022;Manninen et al, 2022;Zeyliger et al, 2022) Tibetan Plateau. For example, an earlier study demonstrated that SM at the depth of 0-10 cm, according to the global land data assimilation system (GLDAS) Noah, can only explain about 71% of the variation in observed SM at the depth of 0-10 cm in Naqu, and the RMSE values between the GLDAS Noah and observed SM were 4.47-5.03 (Chen et al, 2021a).…”
Section: Discussionmentioning
confidence: 47%